Oil palm fibre filled polymer composites for aircraft interior - Ong, Thai Kiat (2025)
This study aimed to assess the feasibility of using natural fibre reinforced thermoplastic composites for aircraft interior components. Currently, aircraft interior components like seats, interior panels, floor coverings, and linings are primarily made from polymeric materials and composites. Synthetic fibre thermoset composites are commonly used due to their excellent mechanical and thermal properties as well as compliance with airworthiness standards. However, recycling thermoset composites is environmentally challenging compared to thermoplastics.